The Development for School Program in order to Encourage Studentsâ Spiritual Intelligence - Hadiana, Hadiana; Hidayat, Syarief; Abdulhak, Ishak (ATIKAN, 2013)
ABSTRACT: Modernity has caused crises of meaning and value. The indictment for productivity, effectiveness and efficiency, material, and instant process is the main characteristic of modern life which has led to the fading of family educational meanings and social values. The development for spiritual intelligence program is expected to decrease the effects of those meaning and value crises. This paper tries to elaborate the roles of educational institution in facing the challenges of modernity in the era of globalization. The research focussed on the Primary School of Al-Azhar Syifa Budi Parahyangan in West Bandung Regency, West Java, Indonesia that has developed a school program named âMumtazâ School. This program consists of 15 activities relating to the indicators for studentsâ spiritual intelligence, which are the ability to draw meaning from an event, the willingness to serve in religious activities, expression of gratitude, the ability to develop social values, the implementation of good deeds, finding and determining life goals, honesty, and patience. Advanced spiritual intelligence will result a noble character of students who serve God, perform social responsibity to themselves, people, and their surroundings. Finally, all stakeholders are responsible to build several characters related to spiritual intelligence, namely politeness, happiness, humbleness, respect, spirit, and discipline.KEY WORD: School programs, spiritual quotient, modernity, moral crisis, primary school, teaching-learning process, and nobility values.IKHTISAR: Artikel ini berjudul âPengembangan Program Sekolah untuk Mendorong Kecerdasan Spiritual Siswaâ. Modernitas telah menyebabkan krisis makna dan nilai. Tuntutan terhadap produktivitas, efektivitas dan efisiensi, kekayaan materi, dan proses instan adalah ciri utama kehidupan modern yang telah menyebabkan pudarnya makna pendidikan dalam keluarga dan nilai-nilai sosial. Pengembangan program kecerdasan spiritual diharapkan dapat mengurangi dampak yang timbul dari krisis makna dan nilai tersebut. Tulisan ini mencoba untuk menguraikan peran lembaga pendidikan dalam menghadapi tantangan modernitas di era globalisasi. Penelitian ini difokuskan pada Sekolah Dasar Al-Azhar Syifa Budi Parahyangan di Kabupaten Bandung Barat, Jawa Barat, Indonesia yang telah mengembangkan program sekolah bernama Sekolah âMumtazâ. Program ini terdiri dari 15 kegiatan yang berhubungan dengan indikator kecerdasan spiritual siswa, yang berkemampuan untuk menarik makna dari suatu peristiwa, kesediaan untuk melayani dalam kegiatan keagamaan, ungkapan rasa syukur, kemampuan untuk mengembangkan nilai-nilai sosial, melakukan perbuatan baik, menemukan dan menentukan tujuan hidup, kejujuran, dan kesabaran. Kecerdasan spiritual selanjutnya akan menghasilkan akhlak mulia siswa yang bertakwa kepada Allah, mampu melakukan tanggung jawab sosial untuk diri mereka sendiri, orang lain, dan lingkungan mereka. Akhirnya, semua pihak bertanggung jawab untuk membangun beberapa karakter yang berhubungan dengan kecerdasan spiritual, yaitu kesopanan, kebahagiaan, rendah hati, saling menghormati, semangat, dan disiplin.KATA KUNCI: Program sekolah, kecerdasan spiritual, modernitas, krisis moral, sekolah dasar, proses belajar-mengajar, dan nilai-nilai mulia.Â Â Â Â About the Authors: Hadiana is a Doctoral Candidate in Educational Cultural Studies at the Faculty of Humanities UNPAD (Padjadjaran University) Bandung, West Java, Indonesia; Prof. Dr. H. Syarief Hidayat is a Lecturer at the Faculty of Humanities UNPAD Bandung; and Prof. Dr. H. Ishak Abdulhak is a Lecturer at the Faculty of Education UPI (Indonesia University of Education) in Bandung. Corresponding author is: hadiana8@yahoo.co.idHow to cite this article? Hadiana, Syarief Hidayat & Ishak Abdulhak. (2013). âThe Development for School Program in order to Encourage Studentsâ Spiritual Intelligenceâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.3(2) December, pp.151-160. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI in Bandung and FKIP UNSUR in Cianjur, West Java, ISSN 2088-1290. Chronicle of the article: Accepted (October 25, 2013); Revised (November 25, 2013); and Published (December 15, 2013).